AsbÄbun NuzÅ«l Surah An-NÅ«r Ayat 2â€“3: Analisis Hukum Zina dan Konsekuensinya dalam Perspektif Al-Qur'an - Rizky Dwi Ratna Septinawati; Mohammad Ari (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Islam categorizes adultery (zinÄ) as a major sin (kabÄÊ¾ir) that threatens the moral order of the family and society. Qurâ€™Än SÅ«rah an-NÅ«r verses 2â€“3 constitute the principal legal foundation for determining sanctions for perpetrators of adultery as well as the related social regulations concerning marriage. This study aims to analyze the asbÄbun nuzÅ«l of SÅ«rah an-NÅ«r verses 2â€“3, to explain the legal provisions on adultery from the perspective of Islamic law, to uncover the social dimensions embedded in these verses, and to examine their relevance in the context of modern society, particularly in Indonesia. This research employs a qualitative method with a tafsÄ«r tahlÄ«lÄ« and historical approach. Primary data are derived from the Qurâ€™Än, á¸¥adÄ«th, and classical Qurâ€™anic commentaries such as the works of al-á¹¬abarÄ«, Ibn KathÄ«r, and al-Zuá¸¥ailÄ«. Secondary data include fiqh literature, contemporary studies on Islamic law, as well as social data from the Indonesian National Population and Family Planning Board (BKKBN) and mass media reports concerning the phenomenon of adultery in Indonesia. The findings indicate that SÅ«rah an-NÅ«r verses 2â€“3 were revealed as a correction to Jewish legal practices and pre-Islamic (JÄhiliyyah) traditions, while simultaneously completing the Islamic legal framework by stipulating the punishment of one hundred lashes for unmarried adulterers (ghairu muá¸¥á¹£an) and stoning for married adulterers (muá¸¥á¹£an). The social dimensions of these verses encompass educational aspects (the public implementation of punishment), preventive aspects (deterring the normalization of adultery), and protective aspects (the prohibition of marrying adulterers without repentance). The relevance of these verses in the modern context remains strong, particularly in addressing contemporary issues such as online prostitution, promiscuity, and the rising incidence of out-of-wedlock pregnancies in Indonesia. SÅ«rah an-NÅ«r verses 2â€“3 offer a comprehensive approach that combines legal firmness, social protection, and a spiritual dimension through the door of repentance.